2015
DOI: 10.6061/clinics/2015(06)02
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity simulation versus case-based discussion for teaching medical students in Brazil about pediatric emergencies

Abstract: OBJECTIVE:To compare high-fidelity simulation with case-based discussion for teaching medical students about pediatric emergencies, as assessed by a knowledge post-test, a knowledge retention test and a survey of satisfaction with the method.METHODS:This was a non-randomized controlled study using a crossover design for the methods, as well as multiple-choice questionnaire tests and a satisfaction survey. Final-year medical students were allocated into two groups: group 1 participated in an anaphylaxis simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 31 publications
1
37
0
3
Order By: Relevance
“…On the other hand, studies that proved the effectiveness of simulation for knowledge acquisition combined this method with other teaching strategies, such as lecture, video, and traditional clinical experience (Hoffmann et al, 2007;Jeffries & Rizzolo, 2006). Studies that compared the effectiveness of simulation with traditional methods obtained similar results to the present research, in which we observed the same performance on evaluations in both groups (Couto, Farhat, Geis, Olsen, & Schvartsman, 2015;Daniels et al, 2010;Downar et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, studies that proved the effectiveness of simulation for knowledge acquisition combined this method with other teaching strategies, such as lecture, video, and traditional clinical experience (Hoffmann et al, 2007;Jeffries & Rizzolo, 2006). Studies that compared the effectiveness of simulation with traditional methods obtained similar results to the present research, in which we observed the same performance on evaluations in both groups (Couto, Farhat, Geis, Olsen, & Schvartsman, 2015;Daniels et al, 2010;Downar et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…A total of 434 papers and abstracts satisfied the search criteria, and 61 papers met the inclusion criteria . The authors scored these 61 manuscripts, and the 10 highest scoring quantitative and two qualitative articles are reviewed below, in alphabetical order by first author's last name.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that studies that were funded tended to be of higher quality when assessed on a validated tool. In 2015, 12 studies (20%) were funded, one received federal funding, two received foundational funding, and eight received support from an institution or unspecified organization . Four of the 12 highlighted articles (33%) this year were funded research …”
Section: Discussionmentioning
confidence: 99%
“…1 Students perceive simulation as a more positive and useful experience for acquisition and retention of knowledge compared to case based discussion. 2 Education Programme We implemented a new in situ simulation programme for the medical students rotating through paediatrics at our hospital with the following aims: 1. To improve students' knowledge, skills and confidence in the assessment, diagnosis and management of acutely unwell children 2.…”
mentioning
confidence: 99%
“…Summary of Product Characteristics review had identified areas of concern regarding patient safety, security and controlled drug documentation. 2 The study aim was to use interprofessional simulation to evaluate the new intranasal diamorphine. To our knowledge, previous use of simulation to identify potential unintended consequences of implementing new medicinal products into practice has not been tested.…”
mentioning
confidence: 99%